Transformasi Ekonomi dan Kemandirian Pangan melalui Penguatan Wanita Kecamatan Gubeng, Surabaya - Augustinah, Fedianty; Sholihah, Nihayatus; Pramudiana, Ika Devy; Ferriswara, Dian (Kadiri University, 2024)
Community service activities aim to empower housewives in Gubeng District, Surabaya, through training and developing entrepreneurial skills in making Rambutan Tahu. With the population continuing to grow, especially in big cities like Surabaya, various challenges arise, especially in terms of poverty and inequality in income distribution. A participatory approach involves participants in identifying their needs and aspirations. The service method involves three main stages: initial survey, implementation, and evaluation. The training was carried out in the PKK environment in Gubeng District, with resource persons from Dr. Soetomo, who provided material and practical guidance to participants. The results show that participants have high enthusiasm for participating in the training, but there are still challenges in applying the skills learned at home. Program evaluation shows increased participants' knowledge and skills, and business opportunities opened, and the availability of business platforms at the neighborhood level. In conclusion, this program has succeeded in having a real impact on improving the welfare of local communities, especially for housewives. The importance of this result lies in its contribution to improving the standard of living and economic value of local communities.Kegiatan pengabdian kepada masyarakat ditujukan untuk memberdayakan ibu-ibu rumah tangga di Kecamatan Gubeng, Surabaya, melalui pelatihan dan pengembangan keterampilan berwirausaha dalam pembuatan Tahu Rambutan. Dengan jumlah penduduk yang terus bertumbuh, terutama di kota besar seperti Surabaya, muncul berbagai tantangan terutama dalam hal kemiskinan dan ketimpangan distribusi pendapatan. Pendekatan partisipatif digunakan untuk melibatkan peserta dalam identifikasi kebutuhan dan aspirasi mereka. Metode pengabdian melibatkan tiga tahap utama: survei awal, pelaksanaan, dan evaluasi. Pelatihan dilakukan di lingkungan PKK di Kecamatan Gubeng, dengan narasumber dari Universitas Dr. Soetomo yang memberikan materi dan bimbingan praktis kepada peserta. Hasil menunjukkan antusiasme peserta yang tinggi dalam mengikuti pelatihan, namun masih terdapat tantangan dalam menerapkan keterampilan yang dipelajari di rumah. Evaluasi program menunjukkan peningkatan pengetahuan dan keterampilan peserta, serta terbukanya peluang usaha dan ketersediaan wadah usaha di tingkat RT. Kesimpulannya, program ini berhasil berdampak nyata dalam peningkatan kesejahteraan masyarakat lokal, khususnya bagi ibu-ibu rumah tangga. Pentingnya hasil ini terletak pada kontribusinya dalam meningkatkan taraf hidup dan nilai ekonomi masyarakat setempat.